Sclerotherapy of a Symptomatic Renal Cyst - Tuğçe Merve Orbay; Hamza Özer; Serdar Moralıoğlu (AVES Yayincilik, 2024)
Simple renal cysts are not commonly found in children. They occur in a small percentage of cases, with an incidence of 0.2%-0.5%. These cysts are typically solitary and develop in the renal cortex. Pain, infection, hematuria, hypertension, or obstruction of the collecting system are indications for treatment. When intervention is necessary, there are several ways to reduce cyst volume. In this report, we discuss the pediatric case of a solitary giant renal cyst and its therapeutic approach. We present a symptomatic pediatric renal cyst patient treated with a sclerosing agent. A simple renal cyst is a rare condition in children, and its treatment includes conservative management, percutaneous sclerosing agent injection, and surgical approach. Choosing the appropriate treatment according to the patient's condition and clinical symptoms is essential. We think that sclerotherapy should be the first-line therapy before surgery in symptomatic simple renal cysts.